Interference DOA estimation and suppression for GNSS receivers using fully augmentable arrays. Issue 3 (1st March 2017) - Wang, Xiangrong; Amin, Moeness; Ahmad, Fauzia; Aboutanios, Elias
Abstract : Multiple antenna receivers have been proposed for interference nulling in Global Navigation Satellite Systems (GNSS). An open‐loop anti‐jam approach is considered and an interference direction‐of‐arrival (DOA) estimation technique using fully augmentable non‐uniform linear arrays is introduced. The DOAs of incoming jammers are estimated utilising the minimum output power method applied to the GNSS receiver coarray and through two different approaches of spectrum sensing and polynomial rooting. Subsequently, the strong interferers are cancelled utilising a subspace projection approach, whereas the 30 dB despreading gain of GNSS receivers protects the satellite signals against weak jammers. Supporting simulation results demonstrate that DOA estimation based on polynomial rooting outperforms spectrum sensing and validate the effectiveness of the proposed anti‐jam strategy.